Os condomínios horizontais fechados e a perspectiva de mobilidade urbana sustentável e inclusiva em Uberlândia-MG - Fernandes, Julieta Cristina (2011)
The objective of this study is to understand the new paradigm of priority to non-motorized transport, based on urban mobility and the knowledge of the infrastructure created for the displacement of the pedestrian in the road space produced within and outside the walls, the closed condominiums are foused. The analyze was concentrated on Uberlândia s Southern Sector of the city, from 1998 to 2009. The procedures used to achieve this objective were: Documentary research at the departments of Urban Planning, Traffic and Transportation and the Municipality of Uberlândia - PMU; field Study with photographic record; conducting semi-structured interviews with the universe of 12 professionals involved with the object of this study case (PMU servers responsible for approving the projects of blends, and professionals responsible for developing architectural and urban projects of condominiums; conducting informal interviews with some residents, service providers and brokers on duty during the visit to the enterprises; making maps in AutoCAD as the spatial survey of condominiums and the distances formed by the occupation of pens and / or closed allotments and have also made several sketches. The results show some negative impacts of the development in Uberlândia - the city object of the case study, where the recently occupied by condominiums / closed allotments subdivisions have not find the necessary between addressing the closure of areas and continuity of road routes. This process occupation by closed areas can lead to disruption of road routes have designed and performed in more peripheral areas. These closed entrepreneurs are located in areas bordering the arterial streets that make up the city\'s main road system. The distance is compensated by the existence of means of quick access to equipment in the region in which they operate and the neighboring or very close areas, causing the walls have extensive meeting and its extension. This research shows that in the Uberlândia s Southern Sector the condominiums have a significant green area and a neighborhood association to the use of grids with the issue of contemplation to the urban land. But maintaining separate in / out. There is a different treatment in the regulations, both in terms of architecture and landscaping, transparencies and bars. But, generally dominated by walls of masonry, forming monotonous landscapes is considered the vast expanses of walls. So, the priority still goes on the motorized and individual travels and more attention should be given to issues relating to non-motorized travel and its priority in the road system.